THE ROLE AND IMPORTANCE OF TAXATION IN THE FORMATION OF GOVERNMENT BUDGET REVENUES - Rafiyeva Zarina Khusanovna; Suyunova Sevinch (Ecominds Press, 2025)
The article analyzes the role and significance of taxes in forming state budget revenues, as well as their impact on economic and social processes. The fiscal, stimulating, distributive, and regulatory functions of taxes are examined from both theoretical and practical perspectives. The study also reviews the oongoing tax reforms in Uzbekistan aimed at modernizing the tax system and strengthening budget stability. The article highlights the strategic importance of taxes in improving public finanacial policy and ensuring economic sustainability.
Keywords: Taxes, state budget, fiscal policy, budget revenues, tax system, tax adminstrationn, economic stability, incentive functions, distribution, public finance.